The acute and chronic effects of "NO LOAD" resistance training - Counts, B. R.; Buckner, S. L.; Dankel, S. J.; Jessee, M. B.; Mattocks, K. T.; Mouser, J. G.; Laurentino, GT. C.; Loenneke, J. P. (Physiology & Behavior, 2016)
The purpose of the study was to remove the influence of an external load and determine if muscle growth can be elicited by maximally contracting through a full range of motion. In addition, the acute physiologic and perceptual responses to each stimulus were also investigated. Thirteen participants completed 18 sessions of unilateral elbow flexion exercise. Each arm was designated to either NO LOAD or HIGH LOAD condition (70% one repetition maximum). For the NO LOAD condition, participants repeatedly contracted as hard as they could through a full range of motion without the use of an external load. Our results show that anterior muscle thickness increased similarly from Pre to Post, with no differences between conditions for the 50% [Pre: 2.7 (0.8) vs. Post: 2.9 (0.7)], 60% [Pre: 2.9 (0.7) vs. Post: 3.1 (0.7)] or 70% [Pre: 3.2 (0.7) vs. Post: 3.5 (0.7)] sites. There was a significant condition × time interaction for one repetition maximum (p = 0.017), with HIGH LOAD (+ 2.3 kg) increasing more than the NO LOAD condition (+ 1 kg). These results extend previous studies that have observed muscle growth across a range of external loads and muscle actions and suggest that muscle growth can occur independent of an external load provided there are enough muscle fibers undergoing mechanotransduction.